LACK OF CONSUMER ADOPTION OF CONVERSATIONAL ROBOTS IN THE ONLINE MARKETPLACE FOR U.S.-BASED CUSTOMERS: A QUALITATIVE STUDY - Okera Jenkins (PEOPLE: International Journal of Social Sciences, 2025)
Artificial intelligence technology continues to grow, with 2025 expected to exceed 17 billion USD in investments. Chatbots, or conversational robots, are a popular form of artificial intelligence technology used in marketing that involves consumer spending projected to surpass 72 billion USD by 2028. However, consumer reactions to chatbots continue to be a challenge despite marketers’ excitement. The problem addressed by this study was the lack of consumer adoption of conversational robots in the online marketplace. The purpose of this qualitative case study was to explore the lack of consumer conversational robots in the position of Facebook users in the United States. The chosen framework for this research was the Technology Acceptance Model (TAM), introduced by Alfred Davis in 1989 to assess users’ attitudes toward technology by measuring their perspectives of perceived use and perceived ease of use. Two research questions were developed to address the research problem. The methodology used was a qualitative case study design, which permitted five open-ended interview questions to answer the two research questions by interviewing 20 participants. Participants were recruited via Facebook, followed by 20 interviews spanning over two months. All interviews were recorded and transcribed using NVivo 15 software and later analyzed using an open-coded inductive thematic analysis to generate categories and themes. Results revealed that consumers desire improved personalization of chatbots and reduced screen interference during their online shopping experiences. Implications of the study indicated the following: 1) perceived usefulness showed no significant relationship with consumers, 2) frustration, annoyance, impatience, intrusiveness, and mistrust were key reasons for avoiding text-based chatbots, 3) user satisfaction with chatbot interactions impacted online purchase intention, 4) consumers perceived chatbots as not useful due to their limited human-like interaction, lack of helpfulness, and inability to address questions sufficiently, and 5) increased anthropomorphism can positively influence user engagement and comfortability. Recommendations for practice and future research include web developers and marketers refining how chatbots are deployed on a webpage, artificial intelligence developers evolving chatbot personalization, and researchers expanding this study by exploring commonalities in specific demographic groups to uncover deeper insights on chatbot adoption.